Plan de Responsabilidad Social Empresarial para la Cooperativa de Ahorro y Crédito “Cristo Rey” de la ciudad de Loja - Songor Ramón, Luis Eduardo (2023)
Corporate Social Responsibility (CSR) is a form of management defined as an ethical and transparent relationship between a company and all its stakeholders, which prioritizes the protection of environmental resources and cultural values, with business objectives compatible with sustainable development. The objective of this work is to evaluate the actions of Corporate Social Responsibility applied in the “Cristo Rey” Savings and Credit Cooperative in the city of Loja. The research has a mixed approach, with an exploratory, descriptive and explanatory scope, due to evaluating CSR through CSR indicators in the social, economic and environmental dimension; For this purpose, information was obtained through a structured questionnaire addressed to the manager and collaborators of the cooperative. The results show that the members of the COAC “Cristo Rey” associate CSR with the improvement of image and quality of work life, likewise, an average knowledge of the dimensions on which CSR is based was determined. On the other hand, the entity complies with nine of the fifteen social actions, four of the economic actions and three environmental actions; However, it does not apply practices related to medical care, disease prevention, annual report, management of workplace sexual harassment, financial economic information and programs to reduce paper consumption. Finally, it is concluded that the cooperative maintains a CSR management model, through social and environmental actions; but there is no specific economic information that allows evaluating its management. Therefore, it is necessary to promote strategies focused on contributing to the strengthening of CSR practices in financial institutions in the Popular and Solidarity Economy sector.